Gypenosides Synergistically Enhances the Anti-Tumor Effect of 5-Fluorouracil on Colorectal Cancer In Vitro and In Vivo: A Role for Oxidative Stress-Mediated DNA Damage and p53 Activation. - Lulu Kong; Xiaobing Wang; Kun Zhang; Wenjuan Yuan; Qiwen Yang; Jianping Fan; Pan Wang; Quanhong Liu (PLoS ONE, 2015)
5-Fluorouracil (5-Fu) has been widely used as a first-line drug for colorectal cancer (CRC) treatment but limited by drug resistance and severe toxicity. The chemo-sensitizers that augment its efficiency and overcome its limitation are urgently needed. Gypenosides (Gyp), the main components from Gynostemma pentaphyllum (Thunb.) Makino, has shown potential anti-tumor property with little side-effect. Here, we carefully explored the chemo-sensitization of Gyp to potentiate the anti-tumor effect of 5-Fu in vitro and in vivo.3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltertrazolium bromide tetrazolium assay and colony formation test reveal that Gyp could significantly enhance the 5-Fu-caused SW-480,SW-620 and Caco2 cells viability loss. Calcusyn analysis shows that Gyp acts synergistically with 5-Fu. Annexin V-PE/7-AAD staining indicates 5-Fu + Gyp could induce SW-480 cell apoptosis. The activations of caspase 3, caspase 9 and poly (ADP-ribose) polymerase (PARP) were involved in the process. Gyp was also found to up-regulate 5-Fu-caused phospho-p53 expression and thus augment 5-Fu-induced G0/G1 phase arrest. Gyp elevated intracellular ROS level, significantly enhanced 5-Fu-triggered DNA damage response as evidenced by flow cytometry, comet assay and the expression of Ser139-Histone H2A.X. Inhibition of ROS and p53 respectively reversed the cell death induced by 5-Fu + Gyp, suggesting the key roles of ROS and p53 in the process. Moreover, 5-Fu and Gyp in combination exhibits much superior tumor volume and weight inhibition on CT-26 xenograft mouse model in comparison to 5-Fu or Gyp alone. Immunohistochemistry analysis suggests the combinations greatly suppressed tumor proliferation. Preliminary toxicological results show that 5-Fu + Gyp treatment is relatively safe.As a potential chemo-sensitizer, Gyp displays a splendid synergistic effect with 5-Fu to inhibit cancer cell proliferation and tumor growth. By using 5-Fu and Gyp in combination would be a promising therapeutic strategy for CRC treatment.